National Survey on Attitudes of Brazilian Breast Surgeons Regarding Oncoplastic Surgery: Success of a Training Model - Cavalcante, Francisco Pimentel [UNESP]; de Oliveira, Vilmar Marques; Ziegelmann, Patrícia Klarmann; Brenelli, Fabrício Palermo; Paulinelli, Régis Resende; Hassan, Augusto Tufi; Novita, Guilherme Garcia; Millen, Eduardo Camargo; Zerwes, Felipe Pereira; Mattar, André; Antonini, Marcelo; Frasson, Antônio Luiz; et al. (Springer Nature, 2025)
BackgroundHistorically, breast reconstruction was performed by plastic surgeons. The Brazilian Society of Mastology (SBM) implemented initiatives to improve breast surgeons’ training in oncoplastic techniques; however, the current proportion of surgeons performing these techniques remained unknown. This study aimed to determine the proportion of Brazilian breast surgeons performing oncoplastic surgery, their previous training, the complexity of procedures performed, and factors influencing adoption of techniques.MethodsIn this survey, a structured questionnaire was sent to all SBM-affiliated breast surgeons between July and December 2023. Outcome proportions were estimated using binomial distribution. Adjusted proportion ratios (aPR) were calculated using robust Poisson regression.ResultsA 60.2% valid response rate was achieved (n = 1059/1759). Almost half of the respondents performed oncoplastic surgery, with most being young (< 40 years) (aPR: 1.66; 1.31–1.10; p < 0.001), male (aPR: 1.39; 1.22–1.59; p < 0.001), southern residents (aPR: 1.39; 1.18–1.63; p < 0.001), with a specialist degree in breast disease (aPR: 1.19; 1.00–1.42; p < 0.004), primarily trained in general surgery (aPR: 1.32; 1.16–1.51; p < 0.001) and secondarily in breast surgery (aPR: 1.41; 1.08–1.85; p = 0.01), and performing > 100 surgeries/year (aPR: 1.72; 1.49–1.99; p < 0.001). The techniques most commonly mastered were simple displacement (88.7%), therapeutic mammoplasty or contralateral symmetrization (96.4%), reconstruction with implants or tissue expanders (93.6%), extreme oncoplasty (81%), skin- and nipple-sparing (99%) or skin-reducing mastectomy (84.2%), and thoracoabdominal flaps (71.7%).ConclusionsA high proportion of Brazilian mastologists perform oncoplastic surgery. These findings provide key insights to further enhance training and improve outcomes.